Education of Philippine Independent Church clergy - Llamoso, Emiliano L.,d1936- (s.n.], 1968)
The purpose of the study is to know how seminarians of the Philippine Independent Church are educated and trained for priesthood at Saint Andrew's Seminary, the only seminary of this Church. The study of relevant documents, interviews, and informal talks with the Dean and members of the faculty, staff, and students of Saint Andrew's Seminary and actual observations of educational activities in the seminary were conducted.